Applying Andragogy Principles to Enhance Professional Development in Corporate Training Programs - Bahrani Bahrani (Yayasan Adra Karima Hubbi, 2024)
Background. Corporate training programs often focus on delivering content without fully considering how adults learn best, leading to limited engagement and skill retention. Andragogy, the theory of adult learning, emphasizes self-directed learning, relevance, and practical application, which could significantly enhance professional development in corporate settings. Despite its potential, the application of andragogical principles in corporate training remains underutilized, limiting the effectiveness of such programs in fostering meaningful skill development and growth. Purpose. This study aims to examine how incorporating andragogy principles can enhance professional development in corporate training programs. Method. A mixed-methods approach was employed, using surveys and interviews with 100 corporate employees who participated in training programs designed with and without andragogical elements. Quantitative analysis was conducted to measure the impact on skill acquisition, engagement, and satisfaction, while qualitative interviews provided insights into the learners’ experiences. Results. The results show that training programs incorporating andragogical principles led to higher engagement and better skill retention compared to traditional methods. Employees reported greater satisfaction and perceived the content as more relevant to their job roles, contributing to improved motivation and a more positive learning experience. Additionally, self-directed learning components significantly boosted long-term retention of skills. Conclusion. In conclusion, applying andragogy principles to corporate training programs enhances the learning experience and leads to more effective professional development outcomes. Organizations seeking to improve the impact of their training initiatives should consider incorporating these principles to foster greater learner engagement and long-term skill retention.